The Papers of Thomas A. Edison From Workshop to Laboratory, June 1873-March 1876 - Edison, Thomas A.; Nier, Keith; Israel, Paul B. (Johns Hopkins University Press, 1991)
The second volume of The Papers of Thomas A. Edison, which covers the inventor's life from the end of June 1873 to the end of March 1876, reveals a remarkable diversity of activities and interests. During his late twenties Thomas Edison pursued his pathbreaking work in telegraph technology, formed a business alliance with the notorious financier Jay Gould, and became embroiled in a bitter legal battle over commercial rights to his quadruplex telegraph. Praise for previous volumes of The Papers of Thomas A. Edison:"The essence of the volume is Edison's technical notebooks, a window onto the inventor's workshop. His lucidity comes through everywhere . . . His writing and drawing come together as a single, vigorous thought process."-Russell McCormmach, New York Times."A mine of material . . . Scrupulously edited . . . No one could ask for more . . . A choplicking feast for Edison biographers-well into the next century, and perhaps beyond."-Fred Howard, Washington Post."A triumph of the bookmaker's art, with splendidly arranged illustrations, essential background information, and cautionary reminders of the common sources on which Edison's imagination drew."-David Joravsky, New York Review of Books."In the pages of this volume Edison the man, his work, and his times come alive . . . A delight to browse through or to read carefully."-Thomas J. Misa, Science.